Genotyping bovine leukemia virus in dairy cattle of Heilongjiang, northeastern China - Yu, Changqing; Wang, Xuefeng; Zhou, Yulong; Wang, Yu; Zhang, Xianfeng; Zheng, Yonghui (BMC veterinary research, 2019)
Background Bovine leukemia virus (BLV) causes enzootic bovine leukosis in cattle and leads to heavy economic losses in the husbandry industry. Heilongjiang Province, China, is rich in dairy cattle. However, its current BLV epidemiology and genotypes have still not been evaluated and confirmed. In this report, we investigated the BLV epidemiology in dairy cattle in the major regions of Heilongjiang Province via the nested PCR assay. Results A total of 730 blood samples were collected from nine different farms in six regions of Heilongjiang. The results showed that the infection rate of these regions ranged from null to 31%. With a clustering analysis of 60 published BLV env sequences, genotypes 1 and 6 were confirmed to be circulating in Heilongjiang. Importantly, a new genotype, 11, and a new subgenotype, 6E, were also identified in the Harbin and Daqing regions, respectively. An epitope analysis showed that a cluster of T-X-D-X-R-XXXX-A sequences in genotype 11 gp51 neutralizing domain 2 was unique among all currently known BLV isolates and was therefore a defining feature of this new genotype. Conclusions BLV epidemics and genotypes were initially investigated in dairy cattle of Heilongjiang. A relatively high infection rate was found in some regions of this province. A new genotype, G11, with a highly specific motif, was identified and thus added as a new member to the current BLV genotype family. This report provides an initial reference for future investigations and subsequent control of BLV transmission and spread in this region.